An alternative approach to community-based ecotourism: a bottom-up locally initiated non-monetised project in Papua New Guinea - Sakata, Hana; Prideaux, Bruce (Journal of sustainable tourism, 2013)
Community-based ecotourism (CBET) is presented as a tool for conservation and sustainable development by conservation practitioners and development agencies, but is reported to have achieved little. Several scholars argue that many problems stem from inadequate power relationships between external actors and local communities, leading to low community participation. This study opens a debate on governance and social enterprise in CBET by examining a bottom-up approach to community-based ecotourism based on a small-scale CBET initiative in an amenity-poor remote indigenous community in Papua New Guinea. This initiative is unique in the following aspects: it was initiated by a community member; external assistance was advisory only; no external financial assistance was given; and it has taken place in a non-monetised economy. Participant observation and in-depth interviews with local key informants were used to identify community-defined positive/negative impacts and community participation processes. Overall, there was substantial support for the project; it contributed to community welfare, generated economic benefit, had positive conservation outcomes and from the viewpoint of the community had no adverse cultural impacts. One of the keys for success was the development of a strong community agency that led to high community participation and individual rather than the community ownership.